1991
DOI: 10.1021/bi00230a035
|View full text |Cite
|
Sign up to set email alerts
|

Secondary nitrogen-15 isotope effects on the reactions catalyzed by alcohol and formate dehydrogenases

Abstract: Secondary 15N isotope effects at the N-1 position of 3-acetylpyridine adenine dinucleotide have been determined, by using the internal competition technique, for horse liver alcohol dehydrogenase (LADH) with cyclohexanol as a substrate and yeast formate dehydrogenase (FDH) with formate as a substrate. On the basis of less precise previous measurements of these 15N isotope effects, the nicotinamide ring of NAD has been suggested to adopt a boat conformation with carbonium ion character at C-4 during hydride tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
32
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
10
32
0
Order By: Relevance
“…29 Similarly, the calculated secondary kinetic isotope effect for 15 N1 gives a value of 1.0042, which is comparable to the experimental value of 1.004 ( 0.001 for hydride transfer from formate to an acetyl-substituted NAD + -model fragment bound to the enzyme. 16 Clearly, these results are in good agreement with the experimental data. This calculated normal value of the secondary 15 N1 kinetic isotope effect further strengthens the proposal that the nitrogen center of the pyridine moiety remains planar in the transition state, 16 as it indicates that the hybridization of N1 is unchanged between the reactants and the transition state.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…29 Similarly, the calculated secondary kinetic isotope effect for 15 N1 gives a value of 1.0042, which is comparable to the experimental value of 1.004 ( 0.001 for hydride transfer from formate to an acetyl-substituted NAD + -model fragment bound to the enzyme. 16 Clearly, these results are in good agreement with the experimental data. This calculated normal value of the secondary 15 N1 kinetic isotope effect further strengthens the proposal that the nitrogen center of the pyridine moiety remains planar in the transition state, 16 as it indicates that the hybridization of N1 is unchanged between the reactants and the transition state.…”
Section: Resultssupporting
confidence: 84%
“…16 Clearly, these results are in good agreement with the experimental data. This calculated normal value of the secondary 15 N1 kinetic isotope effect further strengthens the proposal that the nitrogen center of the pyridine moiety remains planar in the transition state, 16 as it indicates that the hybridization of N1 is unchanged between the reactants and the transition state. Furthermore, the great similarity between the kinetic isotope effects calculated for the gas-phase reaction and the experimental kinetic isotope effect in the enzyme suggests that the transition state for formate oxidation in the enzyme closely resembles the gas-phase transition state structure.…”
Section: Resultssupporting
confidence: 84%
“…It was concluded that hydride transfer taking place in the central ternary complexes is fully rate limiting in the case of these FDHs. A relatively low value of the primary isotope effect observed with NADI (Eo' = -320 mV) as coenzyme was attributed by Cleland and co-workers [62,63,76] to the late transition state of the FDH reaction. The transition state becomes progressively earlier with a change in the redox potential of the coenzyme and is nearly symmetrical in the case of acetylpyridine-NAD+ (Eo'= -258 mV).…”
Section: Isotope Effectsmentioning
confidence: 95%
“…Determination of the secondary deuterium as well as multiple heavy atom (13C, 180, 15N) isotope effects resulted in the formulation of the structure of the transition state ( Figure 2) of the reaction for C. boidinii FDH [62,63,76]. Its main features are: (1) the transition state is linear, and in the case of NADI resembles the products (late transition state); (2) the bending motion of the secondary hydrogen is coupled in the transition state to hydride transfer; and (3) the contribution of tunnelling of both hydrogens in the transition state is significant.…”
Section: Isotope Effectsmentioning
confidence: 99%
See 1 more Smart Citation